2013
DOI: 10.2172/1079766
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of Autoignition in a Jet in a Cross-Flow Configuration: ALCF-2 Early Science Program Technical Report

Abstract: Autoignition in turbulent flows is a challenging fundamental problem due to the intricate coupling of different physical and chemical processes extending over multiple flow and chemistry scales. At the same time, the improved understanding and ability to predict autoignition in flows characterized by considerable fluctuations of velocity, composition, and temperature is essential for the development of novel low-emission concepts for power generation. The aim of this project is to study the fundamental aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Different from the previous simulations conducted by the same code, the flame structure of nonpremixed fuel jet into vitiated crossflow was uniformly stabilized near the jet exit around its entire circumference. Abdilghanie et al reported a 3D DNS of a nitrogen-diluted hydrogen jet injecting into a crossflowing turbulent stream of preheated air and observed that ignition occurred initially at isolated spots downstream from the jet, and later on a burning flame formed near the jet nozzle . Such a reacting JICF configuration is highly interesting, as a large number of factors like the level of dilution would affect the transient behaviors of ignition and reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the previous simulations conducted by the same code, the flame structure of nonpremixed fuel jet into vitiated crossflow was uniformly stabilized near the jet exit around its entire circumference. Abdilghanie et al reported a 3D DNS of a nitrogen-diluted hydrogen jet injecting into a crossflowing turbulent stream of preheated air and observed that ignition occurred initially at isolated spots downstream from the jet, and later on a burning flame formed near the jet nozzle . Such a reacting JICF configuration is highly interesting, as a large number of factors like the level of dilution would affect the transient behaviors of ignition and reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of DNS studies, , the Navier–Stokes equations were solved in their compressible formulation. Since in most cases, a reacting JICF takes place at low Mach numbers, Ma ≪ 1, a large speedup can be obtained using a low-Mach number solver compared to a fully compressible one .…”
Section: Introductionmentioning
confidence: 99%